Journeying together: Improving parent relations within dual-language immersion programs as a model for cross-cultural understanding and collaboration - Porter, Lisa (Journal of Interdisciplinary Studies in Education, 2018)
When visiting Dual Language Immersion (DLI) programs within today’s public schools, sociocultural divides and linguistic barriers between parents of each represented language group become quickly recognizable. Should it be a priority of DLI programs to foster intercultural parental relations as a means for improving student learning? If given the opportunity, would DLI parents participate in such initiatives? If successful, could these efforts be implemented beyond DLI programs to impact entire school communities or even communities at large? Drawing upon data gathered from an extensive case study at an elementary school in Virginia, this paper explores the intercultural relations between DLI parents and the need to re-examine the overall purpose of such programs. Findings revealed strong participant motivation to work collaboratively in establishing relationships and supporting DLI learning opportunities that transcend language instruction for their children to include cross-cultural understanding and a commitment to creating more inclusive communities.